KINETICS OF PHOSPHORUS RELEASE FROM ADDED ROCK PHOSPHATE WITH SOME ORGANIC FERTILIZERS ON CALCAREOUS SOIL. - Naser, K.M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Laboratory experiment was conducted using silty clay loam soil collected from Agriculture fields in Abu Ghraib to study the release of phosphorus from rock phosphate (10.22 P%) on  a soil treated with three types of organic fertilizers namely; peat moss , sheep manure  , poultry manure and  control treatment (soil only). Ten grams of air dried soil  mixed with 100 mg of ground rock phosphate  and  organic fertilizers added at 2.5% level (w:w) were  incubated at a laboratory temperature (298 K ) after adding  water  up  to two-thirds of the field capacity for 40, 90, 120, 150 and 180 days. Citric  acide  soluble  available phosphorous  was estimated after each incubation periods and kinetic equations used to test its release from treated samples. The additions of chicken manure was the highest in the  amount  of  dissolved phosphorus values followed by sheep manure, peat moss, rock phosphate and control treatment, reaching levels of citric  acide  extractable  phosphorus to  4.2 , 3.8, 3.3, 3.1 and 2.5 mg P kg-1 soil, respectively. The results also showed superiority of first  order equation in the description of phosphorus release from rock phosphate with  release  rate   coefficient  of 3.801 , 3.865 , 4.328 and 4.366 mg P kg -1 soil h-1 for the treatments: soil and rock phosphate only , peat moss, sheep waste and chicken manure, respectively.